Methodical approaches to separation of geoecological regions - E V Stanis (RUDN Journal of Ecology and Life Safety, 2012)
The investigation of regional geoecological problems have a big importance for economic development of region. At present does not exist strictly determined united requirements on which possible select geoecological regions. Different methods are used at separation of geoecological region, which hang from problems and scale of the studies.